2018
DOI: 10.1186/s40985-018-0103-x
|View full text |Cite
|
Sign up to set email alerts
|

Health system barriers and levers in implementation of the Expanded Program on Immunization (EPI) in Pakistan: an evidence informed situation analysis

Abstract: BackgroundIn Pakistan, immunization coverage has been quite low since the program’s inception, and the 2012–2013 population-based survey recorded it at 54%. Much has been written about the issues, challenges, and constraints in the implementation of Pakistan’s immunization program. However, there is a need to better understand the health system barriers as well as levers that influence progress. This review aims to bridge the information gaps on system-level barriers that currently impede the optimal delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Findings from the reviews show that half of the countries were experiencing limitations in their human resource capacity within the national program and at sub-national levels. Health worker training plays an important role in improving overall performance including vaccination coverage [ 15 , 16 ]. Other studies and program reviews have also shown the critical role of human resource in immunisation program delivery [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the reviews show that half of the countries were experiencing limitations in their human resource capacity within the national program and at sub-national levels. Health worker training plays an important role in improving overall performance including vaccination coverage [ 15 , 16 ]. Other studies and program reviews have also shown the critical role of human resource in immunisation program delivery [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the reviews show that half of the countries were experiencing limitations in their human resource capacity within the national program and at sub-national levels. Health worker training plays an important role in improving overall performance including vaccination coverage [ 16 , 17 ]. Other studies and program reviews have also shown the critical role of human resource in immunisation program delivery [ 18 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health system barriers in relation to the implementation of the Expanded Program on Immunization (EPI) in Pakistan include problems with program nancing, governance, service delivery, human resources (HR), information systems, and supplies and vaccines [4]. Demand side barriers in Pakistan include low awareness and knowledge of immunization, concerns and misperceptions about vaccines, belief in local remedies and religious beliefs [4].…”
Section: Introductionmentioning
confidence: 99%